Morocco's University Surroundings: Structure and Satisfaction (The International Journal for Scientific Research, 2024)
The current study aims to know the structure and level of satisfaction of Moroccan students with their university surroundings based on the 70-phrase level measure of satisfaction with the university's surroundings, divided into 7 items, Of interest to the various aspects of the university environment, the research sample included 359 students; This made the measurement achieved to achieve a good internal consistency rate of 0.95 alpha Cronbach approach", demonstrating the appropriateness of adopting this measure to study the varying satisfaction with the university environment of this sample. In the same vein, the working analysis of the scale items assures us that the university surroundings are a compilation of two components, the first being a physical element linked to infrastructure, and the other, not a material element encompassing the relational and organizational aspect of the results that show that students are not satisfied with: Facilities and facilities, university services, pedagogical equipment, study process, curricula, and examinations. In return, we find them satisfied with the relationship that brings them together with other colleagues and educational and administrative staff. We have also found that satisfaction clauses are influenced by different sociodemographic variables studied, for example: the level of satisfaction in examinations varies by sex, as does the nature of the student's specialization, as the level of satisfaction with pedagogical methods and curricula changes. It is also clear that the level of education is an effective factor in the student's satisfaction with the quality of the relationship between him and other colleagues and educational and administrative staff, while the student's satisfaction with the teaching process is influenced by the age of the students.
Keywords: University Environment; University Students; Structure; Level of Satisfaction; Anxiety